From rags to riches: how robust is the influence of culture on entrepreneurial activity? - Christian Busch; Andrea Lassmann (ETH Zurich, KOF Swiss Economic Institute, 2010)
Entrepreneurial activity differs substantially across countries. While cultural differences have often been proposed as an explanation, measuring a country's cultural characteristics suffers from various problems. In this paper, we test the hypothesis that cultural factors influence entrepreneurial behavior by looking at differences in self-employment rates between immigrant groups within the same market. Such an approach allows holding constant factors such as the institutional and economic environment. Using U.S. census data for the year 2000, we find significant differences in the propensity to become self-employed across immigrants which is in line with previous findings. However, previous studies could not relate self-employment rates in the U.S. to self-employment shares in the immigrants' home-countries which rejects cultural explanations. We improve over the existing literature by first using a more reasonable proxy for self-employment shares. Second, we additionally account for determinants of self-employment in the immigrants' home countries. Both of these modifications reverse the influence of home-country determinants compared with previous findings. Once we apply our modifications we find evidence of a significantly positive relationship between self-employment rates of immigrants in the U.S. and entrepreneurial activity in their respective countries of origin. Our findings suggest that we cannot reject culture as a major determinant of entrepreneurial activity.
Keywords: J21; J61; L26; 330; culture; entrepreneurship; migration; self-employment; Migranten; Selbstständige; Unternehmer; Kulturpsychologie; USA